How and When to Transition to the Next Phase: Reflections. Issue 5 (11th May 2022) - Tolo, Vernon T.; Weinstein, Stuart L.
Abstract : With Americans living longer, many physicians and surgeons have extended their medical and surgical practice life beyond the traditional 65-year-old retirement age. As retirement is inevitable, planning for that eventuality, which in early practice years appears unnecessary, is in fact an exercise which will pay dividends at the time of retirement. Two senior orthopaedic surgeons provide insight on the 2 main issues concerning retirement: how to prepare for retirement while in active practice, and factors to consider as to the timing of that major life event.